Effect of Some Environmental Conditions on the Inhibitory Activity of Secondary Metabolites of Bacillus spp. Against Biofilm Forming Bacteria - الامارة ايمان عبدالله; الغزاوي غيداء جاسم (The Libyan Journal of Science, 2022)
Fifty water and sediments samples were collected from different locations in Basrah Governorate, southern Iraq. Twenty bacterial spore forming isolates showing antibacterial activity towards gram negative and positive bacteria were isolated from them. The isolates were identified biochemically by VITEK BCL cards and differential tests. The identification results showed that 15 isolates belong to Bacillus subtilis whereas the remaining 5 isolates belong to B. amyloliquefaciens. The isolates were also identified genetically by amplifying gyr A gene which identified the 15 B. subtilis to subspecies rank. Eight isolates were identified as B. subtilis subsp. spizizinii, whereas the remaining 7 isolates were identified as B. subtilis subsp. Subtilis. Also, five biofilm forming bacterial isolates (target bacteria) were isolated and identified by VITEK GB & GN cards. The identification results showed that 3 isolates belong to gram positive bacteria: Staphylococcus sciuri, Methicillin Resistant Staphylococcus aureus (MRSA), and Kocuria kristinae, whereas 2 isolates belong to gram negative bacteria: Pseudomonas aeruginosa, and Escherichia coli. The secondary metabolites (sm) were produced and extracted from Bacillus spp. Results of Thin Layer Chromatography test showed that Bacillus s.m. contain free amino acids. Relative flow (Rf) values showed a relatively close association which ranged between 0.750-0.897. Total proteins were determined by Biuret method, the highest value was for BS8 (13.78 g/L) followed by BS14 (12.02 g/L). Secondary metabolites extracts of BS8 and BS14 were chosen for complete study; s.m. extracts of BS8 and BS14 were purified and results of electrophoresis showed that the molecular weight of BS8 s.m. was 3779 Daltons, while the molecular weight of BS14 s.m. was 694 Daltons. The purified s.m. were identified by GC-MS. The results showed that BS8 s.m. extract contained a number of amino acids and their derivatives as well as lipopeptides which have antimicrobial activity, whereas BS14 s.m. extract contained two compounds which have powerful antibacterial activity against both gram positive and negative bacteria. One of them was an ester the other was a hydrocarbon. The effects of temperature and pH on the antibacterial activity of BS8 and BS14 s.m. extracts against target bacteria were studied, both s.m. showed high thermo stability at the temperature used in the study, but they were inactivated at 121°C, also both s.m. showed high stability to the pH values used in the study.